Gambaran Koping Stress pada Perempuan Pekerja di Gudang Tembakau PT. Perkebunan Nusantara X Kebun Ajung-Jember - Permatasari, Vio Nadya; Dewi, Erti Ikhtiarini; Hadi, Enggal (UPT Percetakan dan Penerbitan Universitas Jember, 2024)
Many working women feel stressed due to their dual roles. Controlling stress requires action to deal with it, namely by focusing on the problem (problem-focused coping) and centering on emotions (emotion-focused coping). This study aimed to determine the description of coping stress in female workers. The population was 800 female workers. The simple random sampling was used with computerized and obtained a sample of 267 workers. The Ways of Coping questionnaire was tested for validity with an alpha value of ≥ 0.70 and reliability using an Alpha Cronbach's value of 0.725 and resulted in 36 valid items. Data were analyzed using univariate analysis. The research ethics test was carried out at the Faculty of Nursing, University of Jember. The results showed that the majority of female workers were aged 26-35 years (40.1%) and married (78.3%) and preferred coping strategies that focused on emotions by 57.7% with the aspect of accepting responsibility (17.2%), compared to coping strategies that focus on problems which is 42.3%. This is because women are more often oriented towards anger. So, when women feel stressed, it is easier to be sad, sensitive, angry, crying, and do anything to release their anger. Promotive activities such as counseling and preventive activities such as counseling could be done to deal with stress.